Impact of Evaluation the internal control system in the economic Institution of Algeria -Study applied for a sample of professionals for the year 2018- (Journal of Economic Additions, 2019)
This study deals with the evaluation of internal control system in the Algerian institutions, intended to identify the internal control system and the main procedures and the evaluation methods in enterprise also exposure the risks that come from its weakness, To reach the objective of the study we collected the statements relying on books, scientific articles, lows and decrees related to the subject and several studies linked to the study, in order to cover the theoretical side of the subject, The practical side was a field study of a sample of practitioners accounting profession and auditing, and a group of professors who are interested in the review, The study also found that the internal control system is a set of procedures and laws laid down by the administration to ensure the good way operations and stability and thus the internal control imperative in all institution. Key words: system control, internal control, economic organization, evaluation.Jel Classification codes: M41.